Understanding social media influence in reviving the trishaw or beca as a popular tourism attraction in Melaka / Siti Hajar Abd Aziz … [et al.] - Abd Aziz, Siti Hajar; Ahmad Ridzuan, Ahmad Nur Azam; Hassan, Mohd Sufiean; Mohd Aslai, Muhammad Syamim; Mazylan Edy, Dania Syafiah (Faculty of Computer and Mathematical Sciences, 2022)
Social media has quickly become an important medium to promote tourism products, such as accommodations, food and beverages, cultural attractions, and entertainment destination. In Melaka, one of the oldest and unique tourist attractions is the trishaw ride or fondly known as beca, a bicycle with a sidecar, powered entirely by the cyclist, which was a popular mode of public transportation in the immediate years following the end of the Japanese Occupation during the year 1942 to 1945. The recent Covid-19 pandemic which enforced movement and travel restrictions saw a decline in the popularity of trishaw rides and deprived the operators of their source of income. While the tourism sector struggles to recover, the operators struggle to continue their tradition of riding trishaw and to keep the cultural heritage alive. This project aimed to study the influence of social media to revive the popularity of trishaw rides in Melaka and help boost the tourism sector. Using purposive sampling and videography as tools, the initial finding shows that social media can be useful to help promote trishaw rides. Respondents agreed that this transportation was still relevant and could help tourists do their sightseeing of popular heritage spots in Melaka, instead of doing it by foot, hence enhancing their cultural appreciation of the Melaka heritage.